Diversidade vegetal em quintais : percepção de estudantes e possibilidades para contextualizar conteúdos botânicos - Alcantara, Kelly Costa de (2023)
Investigating students' perception and knowledge about plant diversity in their daily lives can be a guide for new pedagogical actions that promote a contextualized approach in the teaching and learning process. Students' experience with backyard plants, when present in homes, can be a starting point for teaching botany. This work had the following objectives: to understand the perception of students in relation to the plants present in their backyards; carry out a survey of plant species found in students' homes, their uses and importance and; also propose the contextualization of contents in Science classes. The research involved 22 students from a public school in the urban area of the municipality of Rondonópolis-MT. The following were used as data collection instruments: questionnaires, drawings and photographic records. All students stated that they had a backyard at home and most grow plants. The joint analysis of these instruments revealed that the students partially represented the existing floristic composition in the backyards and in a way that was compatible with reality. However, only 29% of the plants of a total of 80 ethnospecies were identified by their names in the drawings. Most of them are exotic in relation to Brazil. The declared use ethnocategories were: 37% food, 34.5% ornamental and 28.5% medicinal. The results show the importance of pedagogical practices in teaching botany and environmental education that encourage the expansion of students' perception, leading to greater knowledge of the species present in their daily lives. Given the floristic richness found in the surveyed backyards, it can also be concluded that these become important places for students to learn. And in this way, the contextualization of contents about plants can contribute to the realization of more profitable and pleasant Science classes.